Strategi Dalam Meningkatan Pendidikan Wajib Belajar 12 Tahun di Kabupaten Demak - Sintha, Dewi; Warsono, Hardi; Herawati, Agustin Rina; Astuti, Retno Sunu; Afrizal, Teuku (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study aims to examine strategies in improving the 12 year compulsory education. This research was conducted to obtain information related to government support in the implementation of 12 year compulsory education in Demak district. This includes understanding the factors that cause children to drop out of school from internal factors and external factors. Internal factors are due to the lack of family income and the low level of parental education. External factors are caused by environmental factors. Based on the descriptive qualitative approach this research was carried out in Demak Regency. Data collection was carried out through observation and literature study. The results showed that government support for the implementation of the 12 year compulsory education in Demak Regency with the provision of "let's go back to school" starting from primary education to senior secondary education is given to economically disadvantaged students in order to increase student participation in school.